PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK RUMAH TANGGA MEREK TUPPERWARE DI PEKANBARU - Khoiriyah -; Jushermi -; Gatot Wijayanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to determine the effect of variables of brand equity (brand awareness, brand associations, perceived quality of the brand, and brand loyalty) that influence purchasing decisions Tupperware brand household products in Pekanbaru and to know which is the most dominant factor affecting the purchase decision. As for the population in this study are all consumers who ever bought Tupperware brand household products, and samples used in this study amounted to 119 people, and the sampling technique used in this study is the technique Sampling Area. methods of analysis used in this study using multiple linear regression models with SPSS version 17. Based on the results of the research that has been done so that the value of R2 by 57%. This means that 57% of household purchasing decisions brand Tupperware products in Pekanbaru influenced by brand equity (brand awareness, brand associations, perceived quality of the brand, and brand loyalty) while the remaining 43% are influenced by other factors that are not explained and are not included in the study Here you are. and subsequently through a simultaneous regression coefficient test independent variables jointly significant effect on the independent variable .. Partially, of the four variables studied only variable perception of the quality of the brand (X3) are the most significant influence on purchasingKeywords: brand awareness, brand associations, perceived brand quality, brand loyalty and purchasing decisions